Corticofugal projections induce long-lasting effects on somatosensory responses in the trigeminal complex of the rat - Malmierca, Eduardo; Chaves-Coira, Irene; Rodrigo-Angulo, Margarita; Nuñez, Angel (Frontiers in Systems Neuroscience, 2014)
The sensory information flow at subcortical relay stations is controlled by the action of topographic connections from the neocortex. To determinate the functional properties of the somatosensory corticofugal projections to the principal (Pr5) and caudal spinal (Sp5C) trigeminal nuclei, we performed unitary recordings in anesthetized rats. To examine the effect of these cortical projections we used tactile stimulation of the whisker and electrical stimulation of somatosensory cortices. Corticofugal anatomical projections to Pr5 and Sp5C nuclei were detected by using retrograde fluorescent tracers. Neurons projecting exclusively to Pr5 were located in the cingulate cortex while neurons projecting to both Sp5C and Pr5 nuclei were located in the somatosensory and insular cortices (>75% of neurons). Physiological results indicated that primary somatosensory cortex produced a short-lasting facilitating or inhibiting effects (< 5 minutes) of tactile responses in Pr5 nucleus through activation of NMDA glutamatergic or GABAA receptors since effects were blocked by iontophoretically application of APV and bicuculline, respectively. In contrast, stimulation of secondary somatosensory cortex did not affect most of the Pr5 neurons; however both cortices inhibited the nociceptive responses in the Sp5C nucleus through activation of glycinergic or GABAA receptors because effects were blocked by iontophoretically application of strychnine and bicuculline, respectively. These and anatomical results demonstrated that the somatosensory cortices projects to Pr5 nucleus to modulate tactile responses by excitatory and inhibitory actions, while projections to the Sp5C nucleus control nociceptive sensory transmission by only inhibitory effects. Thus, somatosensory cortices may modulate innocuous and noxious inputs simultaneously, contributing to the perception of specifically tactile or painful sensations.